Accelerating progress toward reducing child malnutrition in India: A concept for action - von Braun, Joachim; Ruel, Marie T.; Gulati, Ashok (International Food Policy Research Institute, 2008)
1. The facts: Child malnutrition in India India is home to 40 percent of the world’s malnourished children and 35 percent of the developing world’s low-birth-weight infants; every year 2.5 million children die in India, accounting for one in five deaths in the world. More than half of these deaths could be prevented if children were well nourished. India’s progress in reducing child malnutrition has been slow. The prevalence of child malnutrition in India deviates further from the expected level at the country’s per capita income than in any other large developing country.; 2. The challenge: Accelerating progress in reducing child malnutrition in India India has many nutrition and social safety net programs, some of which (such as Integrated Child Development Services [ICDS] and the Public Distribution System [PDS]) have had success in several states in addressing the needs of poor households. All of these programs have potential, but they do not form a comprehensive nutrition strategy, and they have not addressed the nutrition problem effectively so far.; 3. Strategic choices for improved child nutrition India lacks a comprehensive nutrition strategy. Various choices for nutrition strategies can be considered. A review of some of the more successful country experiences suggests that all of them implemented complex, multisectoral actions with more or less emphasis on service-oriented nutrition policies (as in Indonesia), incentive-oriented nutrition policies linked to community or household participation and performance (as in Mexico), or mobilization-oriented nutrition policies (as in Thailand). These choices are not mutually exclusive. India now has the opportunity to “leapfrog” toward innovative nutritional improvement based on the experiences of other countries and on experiences within India itself.; 4. Cooperation for policy actions To accelerate progress in reducing child malnutrition, India should focus on the following four cross-cutting strategic approaches: a. ensuring that economic growth and poverty reduction policies reach the poor;; b. redesigning nutrition and health policies and programs by drawing on science and technology for nutritional improvement, strengthening their implementation, and increasing their coverage;; c. increasing investments and actions in nutrition services for communities with the highest concentration of poor; and; d. focusing programs on girls’ and women’s health and nutrition. IFPRI, in collaboration with Indian experts and international networks, could bring much-needed experience with programs and policies around the world to bear on this effort. An evidence-based, research-intensive approach with “learning while implementing”—which has shown success in other countries—is recommended. There is no time or reason to wait for taking action.